Direct Medical Costs and Accordance of INA-CBG's Claims on Covid-19 Patients at Anutapura Hospital: Biaya Medis Langsung dan Kesesuaian Klaim Tarif INA-CBG’s pada Pasien Covid-19 di RSU Anutapura - Muhamad Rinaldhi Tandah; Khusnul Diana; Arya Dibyo Adisaputra; Shella Monica; Fatimah Azzahrah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: The pandemic Covid-19 has had an impact on various aspects of life, both socially and economically. One of the government's responsibilities is in financing the treatment of Covid-19 patients, which is stated in the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/5673/2021 regarding technical instructions for claiming the cost of Covid-19 services. Objectives: This study aimed to determine the average direct medical costs and according to the INA-CBGs rates for Covid-19 patients and the effect of length of stay, severity and comorbidities on the total cost from a hospital perspective. Material and Methods: This study was an observational descriptive study, used a sample of patients diagnosed with Covid-19 inpatients at Anutapura Hospital Palu in 2020. The sample was used 134 patients, who met the inclusion and exclusion criteria. The data collected includes patient characteristics, direct medical costs (consultation fees, visits, rooms, medical procedures, medical devices, examinations and drugs) and INA-CBGS rates. Results: the Covid-19 patients were hospitalized for 14 days (65.67%) with severe severity (92.54%), patients without comorbidities (comorbidities) (74.63%) and included in the group with INA-CBGs code was A-4-13-III (92.54%). The average direct medical cost of the patient was Rp. 5,371,333, with the largest cost being the room fee, which was 32.57% of the total cost. The average INA-CBG's tariff was Rp. 123,019,851. Conclusions: The INA-CBGs tariff was higher than direct medical costs with a difference of Rp. 117,648,518. The results of the linear regression test, it was found that there was a partial or simultaneous effect between length of hospitalization, severity and incidence of comorbidities on total direct medical costs.